New and poorly known species of coelotine spiders (Araneae, Amaurobiidae) from Thailand - Dankittipakul, Pakawin; Chami-Kranon, Thanaphum; Wang, Xin-Ping (Zootaxa, 2005)
Two new species of the subfamily Coelotinae (Araneae, Amaurobiidae) are described from Thailand. Coelotes suthepicus sp. n. (% & ) was recorded from an evergreen hill forest near the summit of Doi Pui, northern Thailand. Asiacoelotes sparus sp. n. (%) was collected from a lower montane rain forest on Khao Khieo, Khao Yai National Park, central Thailand. The genus Asiacoelotes Wang, 2002 is reported from this country for the first time, where it presumably reaches its southernmost zoogeographical boundary. Additional specimens of C. thailandensis Dankittipakul & Wang, 2003 are collected from Doi Inthanon National Park; the female of this species is described here; variation in male palpal structure is illustrated. Males of Draconarius monticola Dankittipakul, Sonthichai & Wang, 2005 are collected and described from Doi Chiang Dao.